Value accruing to Zambia’s bean supply chain participants - Mwansa, Martin C. (Kansas State University, 2013)
The purpose of this thesis was to estimate the value accruing to Zambian bean supply chain participants with the view to showing that value at the different stages is a function of the value addition and risk incurred at those stages. The data used in the study came from two different surveys done under the Pulse Value Chain Initiative – Zambia focusing on producers and bean traders. The surveys used structured questionnaires for both producers and traders. The producers were sampled from three principal bean producing provinces in Zambia: Lundazi, Mbala and Kalomo. The traders were sampled from the largest consumer region in the country – Lusaka – and focused on traders operating in the three principal markets in the city: Soweto; Chilenje; and Mtendere. The analyses were conducted using STATA®, employing both statistical and econometric methods. Value was defined as a function of transaction costs and value addition as well as the risks borne. In the Zambian mixed bean trade environment, where traders travel to remote locations where producers live and produce, they are seen to incur higher levels of risk and undertake higher levels of value addition – assembling the grain, bagging them and moving them from the rural areas where production occurs to the cities where customers reside. As such, it is expected that value creation and distribution would increase away from the farm. The results confirmed this expectation. The total average value created at the farm level was ZMK3,391.06/kg. However, the average value accruing to traders who only undertook wholesaling was ZMK7,405.75/kg while that accruing to traders going further down the chain to retail was ZMK9,663.56/kg. Traders who engaged in institutional trade produced an average value of ZMK8,750.75/kg. The share of total value produced accruing to producers in the producer-wholesaler-retailer chain was about 16.6 percent because of the higher value addition and risk that occur further downstream in the chain. The share of total value produced accruing to producers in the producer-wholesaler-institutional buyer chain was about 17.3 percent. The study showed that female producers’ share was not different, statistically speaking, from male producers’ value. It also showed that the average value created in thin (smaller) markets was higher than the value created in larger markets, probably because of the level of competition that occurs in the latter markets. Interestingly, the results showed that the larger the land holdings of producers, the lower the value created. This is in line with the foregoing results of size, competition and value. The study suggests that producers’ share of total value created may be enhanced by helping producers undertake specific activities that increased the value they added and reduce the risks that traders bear in their search for grain. One of such activities could be the formation of horizontal strategic alliances among producers that allowed producers to aggregate grain at particular locations in significant lots and bag them. This service would allow them to extract higher value from the exchange with traders. Any attempt to address the perceived “unfair” distribution of value along the supply chain by administrative fiat could result in higher costs to the whole supply chain and crate adverse unintended consequences for producers and the treasury.
Keywords: Supply chains; Value distribution; Transaction cost; Mixed beans; Zambia; Agriculture, General (0473); Economics, Commerce-Business (0505); Management (0454)